2023
DOI: 10.3390/ijerph20032176
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Alcohol Consumption in Slovak Cities during the COVID-19 Lockdown by Wastewater-Based Epidemiology

Abstract: The consumption of alcohol in a population is usually monitored through individual questionnaires, forensics, and toxicological data. However, consumption estimates have some biases, mainly due to the accumulation of alcohol stocks. This study’s objective was to assess alcohol consumption in Slovakia during the COVID-19 pandemic-related lockdown using wastewater-based epidemiology (WBE). Samples of municipal wastewater were collected from three Slovak cities during the lockdown and during a successive period w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Analysis of the overall alcohol consumption during each of the COVID Alert levels revealed that there was no evidence of a significant difference in mean alcohol consumption between the highest restriction (Level 4) and lowest restriction, Level 1 ( p ‐value=0.25) (Figure 4). Our observation of no increase in consumption under enforced social restrictions and lockdowns/stay‐at‐home orders is in line with that seen in studies in Australia, Austria, Belgium, Slovakia and Spain who report a stable or decrease in alcohol consumption in their WBE‐based studies, as well as subsequent increases in consumption once restrictions eased [33–38] …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Analysis of the overall alcohol consumption during each of the COVID Alert levels revealed that there was no evidence of a significant difference in mean alcohol consumption between the highest restriction (Level 4) and lowest restriction, Level 1 ( p ‐value=0.25) (Figure 4). Our observation of no increase in consumption under enforced social restrictions and lockdowns/stay‐at‐home orders is in line with that seen in studies in Australia, Austria, Belgium, Slovakia and Spain who report a stable or decrease in alcohol consumption in their WBE‐based studies, as well as subsequent increases in consumption once restrictions eased [33–38] …”
Section: Resultssupporting
confidence: 90%
“…Our observation of no increase in consumption under enforced social restrictions and lockdowns/ stay-at-home orders is in line with that seen in studies in Australia, Austria, Belgium, Slovakia and Spain who report a stable or decrease in alcohol consumption in their WBE-based studies, as well as subsequent increases in consumption once restrictions eased. [33][34][35][36][37][38] The Impact of COVID-19 Report (2020) was a survey conducted by Te Whatu Ora j Health Promotion (formerly Te Hiringa Hauora j Health Promotion Agency j Te Hiringa Hauora) between the 7th and 13th of April 2020, i. e., during the first COVID-19 Alert Level 4 Lockdown (not during the time period covered in this study). In this survey, 34 % of respondents selfreported consuming less alcohol than usual, 19 % report consuming more alcohol than usual, and almost half (47 %) consumed their usual amount.…”
Section: Impact Of Covid Lockdowns On Alcohol Consumptionmentioning
confidence: 99%
“…That indicates that the restrictions might have caused an increase in alcohol consumption. Other authors have observed an opposite relationship-due to the shutdown of the hospitality industry and cancellation of events, common places and occasions for social drinking of alcoholic beverages were not available; consequently, alcohol consumption in Innsbruck, Austria, dropped from 12.6 to 9.9 kg day −1 1000 inh −1 [3], and in selected Slovak cities during the lockdown, it was reported to decrease ca 20% compared to the period of milder restrictions [38]. However, it is important to note that the relationship between pandemic limitations and alcohol consumption is complex.…”
Section: Alcoholmentioning
confidence: 96%